Immunogenicity and safety of a combined DTPa-IPV/Hib vaccine administered as a three-dose primary vaccination course and a booster dose in healthy children in Russia: a phase III, non-randomized, open-label study - Victor Romanenko; Irina Osipova; Anna Galustyan; Michael Scherbakov; Nathalie Baudson; Déborah Farhi; Luis Anaya; Sherine O. Kuriyakose; Nadia Meyer; Winnie Janssens (Taylor & Francis Group, 2020)
We assessed the immunogenicity and safety of the combined diphtheria-tetanus-acellular pertussis-inactivated poliovirus/Haemophilus influenzae type b vaccine (DTPa-IPV/Hib) in children in Russian Federation aiming to support the registration of the vaccine in Russia. In this phase 3, non-randomized, open-label study (NCT02858440), healthy children received three primary doses at 3, 4.5, and 6 months of age (N = 235) and a booster dose at 18 months of age (N = 225). Seroprotection rates against diphtheria, tetanus, Hib, and poliovirus 1-3, seropositivity rates against pertussis antigens, and antibody geometric mean concentrations/titers for all antigens were evaluated one month post-primary and post-booster vaccinations. Solicited local and general adverse events (AEs) were collected during a 4-day period and unsolicited AEs during a 31-day period post-vaccination. Serious AEs were recorded throughout the study. At post-primary vaccination, all infants were seroprotected against diphtheria, tetanus, and poliovirus 1 and 2, 99.3% against poliovirus 3, and 98.4% against Hib. At least 98.9% of participants were seropositive for the three pertussis antigens. At post-booster vaccination, all toddlers were seroprotected/seropositive against all vaccine components. The most frequent local and general solicited AEs were redness, reported for 52.6% and 44.9% of children, and irritability, reported for 64.7% and 39.1% of children, post-primary and post-booster vaccination, respectively. Unsolicited AEs were reported for 20.4% (post-primary) and 5.8% of children (post-booster vaccination). Most AEs were mild or moderate in intensity. Six serious AEs were reported in three (0.4%) children; none were fatal or assessed as vaccination-related. DTPa-IPV/Hib proved immunogenic and well tolerated in the Russian pediatric population.